The Implementation Of Problem Solving Model Using Numbered Heads Together In The Teaching Circle Subject Viewed From Student's Adaptive Reasoning In Smp Negeri 1 Surakarta - Oktaviani, Ike Zetti, Dra. Nining Setyaningsih, M.Si (2013)
The purpose of this research is to analyze: 1) the effect of learning model of Problem Solving model using Numbered Heads Together (NHT) and the conventional learning modelfor student's mathematics achievement, 2) the effects of low, medium, and high adaptive reasoning to student's mathematics achievement, 3) the interaction of learning modeland student's adaptive reasoning to student's mathematics achievement. The populations are all students of grade VIII in SMP Negeri 1 Surakarta (8 classes). Sample in this research consist of 2 classes, there are class C as control class with 27 students and class D as experiment class with 25 students. The sampling technique use in this research is cluster random sampling. In effor t to obtain the necessary data in this research, researchers use the test method there are questionnaire method and auxiliary method. Technique of data analysis uses two ways variance analysis test with unequal cell, a prerequisite using Liliefors test to analysis normality test and Bartlett test to analysis homogeneity test. The result of data analysis with significant level 5% satisfied that: 1) there is no significant effect of students that are given problem solving model using numbered heads together with students that given conventional model to the student's mathematics achievement. This is based on analysis of data with F a =? ????? < F table =4,056. 2) There is significant effect of adaptive reasoning of students to the student's mathematics achievement. This is based on analysis of data with F b =?????? > F table =3,206. 3) There is no significant effect of interaction solving model using numbered heads together and conventional model viewed from student's adaptive reasoning to the student's mathematics achievement. This is based on analysis of data with Fab = ? ???? ? Ftable =3,206.